Teaching english to very young learners through authentic communicative performances - Guevara, Diana Carolina; Ordoñez, Claudia Lucia (Colombian Applied Linguistics Journal, 2012)
We present here the results for the kindergarten level of a qualitative research study on the impact of a curriculum connecting learning events in Spanish and English in authentic communicative performances. The school in the study was a private institution in a mid-sized Colombian city. The curriculum is based on communicative and constructivist principles and presents the learning events as communicative authentic performances. We describe the performances that the kindergarten teachers developed based on the curriculum, how they achieved authenticity in them, and their impact on the students’ attitude towards the English class and on their learning. We analyzed four teacher interviews and four class observations done over a year, plus two more class recordings made independently by the teachers. They reveal that teachers used a variety of games, especially role-playing games developed from ideas from the children, reading of stories, and songs and that the students became enthusiastic and active and improved their oral skills considerably.